Calcifying fibrous tumor of the ileum resected by single-port laparoscopic surgery: a case report - Kazuya Takabatake; Tomohiro Arita; Yoshiaki Kuriu; Hiroki Shimizu; Jun Kiuchi; Wataru Takaki; Hirotaka Konishi; Yusuke Yamamoto; Ryo Morimura; Atsushi Shiozaki; Hisashi Ikoma; Takeshi Kubota; et al. (Surgical Case Reports)
Abstract Background Calcifying fibrous tumors (CFTs) are rare benign tumors. Because CFTs sometimes relapse, radical resection with adequate margins is necessary. We report a case of ileal CFT resected using single-port laparoscopic surgery. Case presentation A 33-year-old man presented with chief complaints of abdominal pain and vomiting. Computed tomography demonstrated a 45-mm-sized pelvic mass with partial calcification in the ileum. The patient was diagnosed with an ileal tumor, and partial resection of the ileum was performed using the single-port laparoscopic technique. Pathologic findings revealed hypocellular spindle cells with dense hyalinized collagen, interspersed calcification, and infiltration of lymphoplasmacytic cells. Immunohistochemical analysis showed that the factor XIIIa was positive and other tumor-specific markers were negative. Based on these findings, the tumor was finally diagnosed as a CFT. Conclusions Although CFT is benign, multifocal and recurrent CFTs have been reported. Therefore, careful intraperitoneal observation and curative resection are necessary. Single-port laparoscopic surgery is acceptable, both in terms of curability and minimal invasiveness.